A 55-year trajectory of the most influential specialist in the History of Colonial Brazil: an interview with Stuart B. Schwartz (Revista de Estudios Brasileños, 2023)
Interview with Professor Stuart B. Schwartz, George Burton Adams Professor at Yale University (New Haven, Connecticut). In this interview, Prof. Schwartz reflects upon his academic career, discusses his life-time engagement with the history of Brazil, presents his current concerns as a professor and researcher, discloses his future projects and analyzes the current situation of Brazil and its historiography.